2018
DOI: 10.1016/j.bbagen.2018.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 potentiates FcεRI-induced PGD 2 biosynthesis and induces VEGF from human in situ -matured skin mast cells

Abstract: These findings from this study indicate that IL-6 contributes to human allergic disease by enhancing the production of inflammatory PGD from tissue-resident mast cells. Moreover, the data suggest a novel role for IL-6 in mast cell-mediated angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 54 publications
3
40
0
Order By: Relevance
“…It also leads to recruitment and differentiation of mast cells, as well as monocytes, CD4+ and CD8+ T cells, and B lymphocytes, and it stimulates the production of VEGF by fibroblasts. IL-6 expression affects the homeostatic processes that is related to tissue injury and activation of stress-related responses [40][41][42][43]. Despite being an anti-inflammatory cytokine, the expression of IL-10 was increased in ZIKV-infected HMC-1 cells, which corroborates what was observed in another study, in the serum of Zika positive patients [44].…”
Section: Discussionsupporting
confidence: 82%
“…It also leads to recruitment and differentiation of mast cells, as well as monocytes, CD4+ and CD8+ T cells, and B lymphocytes, and it stimulates the production of VEGF by fibroblasts. IL-6 expression affects the homeostatic processes that is related to tissue injury and activation of stress-related responses [40][41][42][43]. Despite being an anti-inflammatory cytokine, the expression of IL-10 was increased in ZIKV-infected HMC-1 cells, which corroborates what was observed in another study, in the serum of Zika positive patients [44].…”
Section: Discussionsupporting
confidence: 82%
“…IL-6 is a pro-inflammatory molecule and mediates stroke-induced inflammation [40][41][42] and also increases MCs maturation [43]. IL-6 also upregulates histamine production and induces the FceR1 immunoglobulin receptor found on mast cells [44][45][46][47]. In addition, we found that mucus secreting fucosylated goblet cells were reduced after stroke in Ag mice.…”
Section: Discussionmentioning
confidence: 99%
“…stroke-induced inflammation [40][41][42]. IL-6 increases MCs maturation [43] by inducing the FceR1 receptor on MCs [44][45][46][47] and by upregulating HA production. In young mice, we found increased levels of plasma IL-6 at 6 hours post-stroke that normalized by 24 hours, when compared to age-matched shams.…”
Section: Stroke-induced Ha Release Is Associated With Increased Pro-imentioning
confidence: 99%
“…The high expression of PTGS2 can promote large amount of PGD2 synthesis and aggravate the in ammatory response in CSU patients. Besides, IL6 classical signaling can also enhance the expression of COX2 induced by FcεRI, which thereby enhances the production of IgEdependent PGD2 by human tissue-derived mast cells [36]. It is well known that endothelial dysfunction may increase vascular permeability, leading to a pro-in ammatory response.…”
Section: Discussionmentioning
confidence: 99%